(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This cross-sectional study examined associations between nutritional status and reproductive outcomes in 240 women of reproductive age at an urban clinical center in Uzbekistan. Deficiencies in iron, vitamin D, and elevated glycemic load demonstrated statistically significant correlations with menstrual irregularity, anovulation, and hormonal imbalance. Findings underscore the necessity of integrating nutritional assessment into standard reproductive health protocols.